Late Pleistocene sedimentary environment reconstruction and evolution in the Houtao Plain - Li, Fuqiang; Pang, Hongli; Gao, Hongshan (Frontiers in Earth Science, 2023)
Reconstructing the Late Pleistocene sedimentary environment history of the Houtao Plain has great significance not only for revealing the evolution of the Yellow River but also for identifying the formation of paleolake and the northern Ulan Buh Desert. This paper presents the results of the sedimentary facies framework based on a grain-size multi-parameter analysis optically stimulated luminescence and 14C dating for a drilling core DKZ06 with a length of 20.04 m from the Houtao Plain. Grain-size multi-parameter analysis was combined with the grain size of modern environmental sediments to the division of the core sedimentary facies in this area. Sedimentary facies of core DKZ06 indicate that the formation of the Houtao Plain area is dominated by fluvial channel deposition and river changed mainly by frequent fluvial channel since ∼35 ka. The two episodes of shallow lake deposition from a drilling core, suggesting that there will not be a mega-paleolake in the Houtao Plain, and the frequent channel migration of the Yellow River may have caused a series of furiotile lakes during the Late Pleistocene. The appearance of aeolian sand at the top of core DKZ06 combined with previous stratigraphic records from the adjacent areas indicates that the origin of the northern Ulan Buh Desert is relatively late and it formed only 2,000 years ago. We propose that a combination of river migration and large-scale human activity may be responsible for desert formation. The evolution of sedimentary environments has a close correlation with climate change during the Late Pleistocene. During the interglacial stage (MIS3), the sedimentary environment has a particular lacustrine and fluvial–lacustrine environment because of relatively warm–humid conditions. During the glacial stage (MIS2), the Houtao Plain was dominated by a fluvial sedimentary environment because of a relatively cold and dry climate. The sedimentary environment is complex and changeable during the Holocene (MIS1), which was likely due to the frequent climate fluctuation.